2020
DOI: 10.1002/ppul.25104
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of exercise‐induced bronchoconstriction and laryngeal obstruction in adolescent athletes

Abstract: Objectives To study the prevalence of exercise‐induced bronchoconstriction (EIB) and exercise‐induced laryngeal obstruction (EILO) in adolescent athletes. Methods All adolescents (n = 549) attending first year at a sports high school in 2016 and 2017, were invited to answer a questionnaire on respiratory symptoms. The 367 responding participants were divided into two groups based on whether they reported exercise‐induced dyspnea (dyspnea group) or not (nondyspnea group). Randomly selected participants in each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 37 publications
(57 reference statements)
0
40
0
Order By: Relevance
“…An estimated 20%–40% of otherwise healthy runners experience EID even at low absolute exercise intensities ( Johansson et al, 2015 ; Smoliga et al, 2016 ; Ersson et al, 2020 ). This could be because unfit or deconditioned individuals may approach high levels of exertion and experience limb fatigue at low absolute workloads ( Abu-Hasan et al, 2005 ).…”
Section: Respiration During Exercisementioning
confidence: 99%
“…An estimated 20%–40% of otherwise healthy runners experience EID even at low absolute exercise intensities ( Johansson et al, 2015 ; Smoliga et al, 2016 ; Ersson et al, 2020 ). This could be because unfit or deconditioned individuals may approach high levels of exertion and experience limb fatigue at low absolute workloads ( Abu-Hasan et al, 2005 ).…”
Section: Respiration During Exercisementioning
confidence: 99%
“…EILO is a less well-known diagnosis, and therefore possibly less likely to be considered. Ersson et al found an estimated prevalence of EIB in 23% and EILO in 8% of adolescents attending first year of sports high school in Sweden, underlining the importance of EILO as differential diagnosis to EIB ( 58 ). In two other Scandinavian studies of unselected children with exercise related complaints, the EILO prevalence was 5% and 7.5% ( 5 , 6 ).…”
Section: Exercise Induced Laryngeal Obstructionmentioning
confidence: 99%
“…Around 5% of the adolescent population experience an inspiratory airflow limitation during exercise due to inappropriate closure of the larynx: EILO ( 1 , 40 ). It is a frequent, but underdiagnosed cause of exertional dyspnea that mainly affects adolescent, female athletes ( 41 ).…”
Section: Introductionmentioning
confidence: 99%